Effects of intensive longitudinal data collection on pregnancy and contraceptive use. Issue 2 (3rd March 2016) - Barber, Jennifer S.; Gatny, Heather H.; Kusunoki, Yasamin; Schulz, Paul
Abstract : We use an experiment based on the relationship dynamics and social life study of sexual behavior, pregnancy, and contraceptive use to investigate whether participation in weekly self-reports over one year result in differential effects on related behaviors and attitudes, compared to participation in a one-time follow-up interview requiring retrospective self-reporting for the prior year. We randomly assigned 200 subjects to either a control group or a journal group. All subjects were interviewed at the beginning of the study (baseline interview) and 12 months later (closeout interview). Subjects in the journal group also completed a five-minute web- or phone-based survey every week during the 12-month study period. We found no statistically significant difference in pregnancy rates across the two groups at closeout. Contrary to our expectation, the control group experienced a slightly larger increase in having ever used a contraceptive method, although this was mainly due to increases in the least effective methods, such as condoms and withdrawal. Respondents in the weekly interview group became slightly more positive toward childbearing in terms of one specific attitude measure, but not for the vast majority of measures. We conclude that intensive longitudinal data collection does not appear to have a large or consistent impact on respondents' pregnancy, contraceptive use, or related attitudes, relative to the more standard longitudinal approach.